Effects of virtual reality-based interventions on cognitive function, emotional state, and quality of life in patients with mild cognitive impairment: a meta-analysis - Li, Xiaohan; Zhang, Yuting; Tang, Lifeng; Ye, Lin; Tang, Min (Frontiers in Neurology, 2025)
ObjectivesThis meta-analysis aims to systematically evaluate the effects of virtual reality (VR)-based interventions on cognitive function, emotional state, and quality of life in patients with mild cognitive impairment (MCI).MethodsA comprehensive literature search was conducted using five databases from their inception to June 2024. The inclusion criteria focused on randomized controlled trials (RCTs) that examined VR-based interventions in adults aged 60 or older diagnosed with MCI. The primary outcome was cognitive function, while secondary outcomes included emotional state, quality of life, and dynamic balance. To investigate potential sources of heterogeneity, subgroup analyses and meta-regression were conducted. Subgroup analyses were stratified by VR parameters (immersion level, duration, session, and frequency) and demographic factors (geographic region, education level, and male proportion). Publication bias was assessed using funnel plots and Egger’s regression test. A “trim and fill” method was employed to adjust for any detected publication bias. The certainty of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework with the GRADEpro GDT software.ResultsA total of 30 RCTs involving 1,365 participants from 9 countries across 4 continents were included. The meta-analysis revealed that VR-based interventions significantly improved global cognition, as assessed by the Montreal Cognitive Assessment (MoCA; SMD = 0.82, 95% CI: 0.27 to 1.38, p = 0.003, GRADE: moderate) and the Mini-Mental State Examination (MMSE; SMD = 0.83, 95% CI: 0.40 to 1.26, p = 0.0001, GRADE: low). Additionally, VR interventions enhanced attention, as measured by the Digit Span Backward (DSB; SMD = 0.61, 95% CI: 0.21 to 1.02, p = 0.003, GRADE: low) and Digit Span Forward (DSF; SMD = 0.89, 95% CI: 0.34 to 1.45, p = 0.002, GRADE: low). Improvements were also observed in quality of life, as indicated by scores on the Instrumental Activities of Daily Living (IADL; SMD = 0.22, 95% CI: 0.00 to 0.45, p = 0.049, GRADE: moderate). However, no significant effects were found for executive function, memory, verbal fluency, visual abilities, emotional status, or dynamic balance (p > 0.05). Subgroup analysis revealed that VR interventions were more effective when using semi-immersive VR, with session durations of ≤60 min and a frequency of more than twice per week. Participants from Asia and Europe demonstrated better outcomes, and a lower proportion of male participants (≤ 40%) was also associated with improvements in targeted cognitive domains.ConclusionThe findings indicate that VR interventions can significantly improve global cognition, attention, and quality of life in individuals with MCI. Subgroup analyses further revealed that optimal cognitive outcomes were associated with semi-immersive VR, session durations of ≤60 min, intervention frequencies exceeding twice per week, studies conducted in Asia and Europe, and participant groups with a male proportion of ≤40%. Moreover, the study provides valuable insights into secondary outcomes, suggesting that VR interventions may positively impact emotional state and dynamic balance when appropriately tailored to factors such as immersion level, duration, frequency, and other relevant parameters.